Modernization movement in the social field And the transportation and urbanization sector In Saudi Arabia [1953-1916] (Journal of the College of Basic Education, 2022)
1- The social field:A- Health:Prior to the introduction of modern methods of medicine, the Kingdom did not know health care mattersPeople did not have doctors, and hospitals were the reference for patients and people with disabilities, and most of whatThere are methods of medical treatment, psychological suggestion, and the dependence of the Najdis on herbs in treatmentpatients and surgical dressing methods that are too risky; often led toThe death of the injured person or the disabling of one of his organs; There was no health care in HijazBeing reassured about it, as the pilgrims were visiting the Sacred House of God and visiting the tomb of the best of mankindThey face the most severe difficulties in the event of illness, and hundreds of people die from them every year. due to blightThe sun, deadly epidemics, and the use of dirty water